Insya' Muwajjah Approach for Arabic Writing in Elementary School: Pendekatan Insya' Muwajjah untuk Menyempurnakan Pembelajaran Menulis Bahasa Arab di Sekolah Dasar - Sholikhah, Maya; Ammar, Farikh Marzuki (Indonesian Journal of Education Methods Development, 2023)
This qualitative research with a descriptive approach investigates the application of the Insya' Muwajjah approach to writing learning at Mi As-Syafi’iyah Tanggul, focusing on fourth-grade students. Employing interviews, observations, and documentation, the study reveals a structured process encompassing preparation, implementation, and evaluation stages. The study's outcomes highlight supportive factors, such as teacher facilitation and educator competence, while inhibiting factors include motivation, educational background, and vocabulary limitations. By enhancing writing skills through the Insya' Muwajjah approach, this research offers insights into optimizing Arabic language education. Highlights: Effective Pedagogical Approach: The study explores the implementation of the Insya' Muwajjah approach, shedding light on its effectiveness in enhancing Arabic writing skills among elementary school students. Supportive and Inhibiting Factors: The research identifies key factors facilitating the successful integration of the Insya' Muwajjah approach, such as teacher facilitation and educator competence, while also highlighting challenges like motivation, educational background, and vocabulary limitations. Optimizing Language Education: By analyzing the application of the Insya' Muwajjah approach, the study provides valuable insights for educators and curriculum developers aiming to optimize language education strategies, particularly in teaching Arabic writing, at the elementary level. Keywords: Insya' Muwajjah approach, Arabic writing learning, elementary school, qualitative research, language education.